Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Synthesis of the aminocyclitol units of (-)-hygromycin a and methoxyhygromycin from myo-inositol - Gurale, Bharat P.; Shashidhar, Mysore S.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2012)
Concise and efficient syntheses of the aminocyclitol cores of hygromycin A (HMA) and methoxyhygromycin (MHM) have been achieved starting from readily available myo-inositol. Reductive cleavage of myo-inositol orthoformate to the corresponding 1,3-acetal, stereospecific introduction of the amino group via the azide, and resolution of a racemic cyclitol derivative as its diastereomeric mandelate esters are the key steps in the synthesis. Synthesis of the aminocyclitol core of hygromycin A involved chromatography in half of the total number of steps, and the aminocyclitol core of methoxyhygromycin involved only one chromatography.